2015
DOI: 10.1159/000371541
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Encephalitis Caused by Disseminated Aspergillus Infection after Orthotopic Liver Transplantation

Abstract: Liver transplantation is the only available treatment for some patients with end-stage liver disease. Despite reduction in mortality rates due to advances related to surgical techniques, intensive medical management and immunosuppressive therapy, invasive fungal infections remain a serious complication in orthotopic liver transplantation. We report the case of an 18-year-old male diagnosed with autoimmune cirrhosis in 2009 who was assessed and listed for liver transplantation for massive variceal hemorrhage. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Consistent with the ndings of some previous studies [10,[15][16][17][19][20][21][22][23][24][25][27][28], our study found illness course,use of advanced antibiotics,use of chemotherapy or immunosuppressants,surgical history and pulmonary bacterial infection as important risk factors of pulmonary fungal infections for PTB patients.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the ndings of some previous studies [10,[15][16][17][19][20][21][22][23][24][25][27][28], our study found illness course,use of advanced antibiotics,use of chemotherapy or immunosuppressants,surgical history and pulmonary bacterial infection as important risk factors of pulmonary fungal infections for PTB patients.…”
Section: Discussionsupporting
confidence: 92%
“…While specific pulmonary imaging findings can be suggestive of IA, it has recently been noted that radiologic findings of invasive mold infections among solid organ transplant recipients are more varied than previously thought and CNS IA has no consistent radiographic appearance. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Additionally, serum galactomannan, which was negative in our patient, is only 55.6% sensitive and 93.9% specific for IA in liver transplant patients. 28 While our patient was an organ recipient, he had no typical clinical or chest imaging findings of IA, no specific brain imaging findings of IA and a negative serum galactomannan.…”
Section: Discussionmentioning
confidence: 91%
“…Upon performing a PubMed-based literature review dating from 2005 to present, we identified19 previously reported cases of CNS IA in patients with liver disease of any kind (Table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Most patients were male with a median age of 38 (range 12 to 68). Four of the 19 patients never received a transplant, and had severe liver with CSF PCR, while in two cases, diagnosis was inferred from cultures from other sites.…”
Section: Liter Ature Re Vie Wmentioning
confidence: 99%
“…are one of the most frequent fungi isolated from neurological infections, most infections of the CNS are due to A. fumigatus, which gets into the CNS by hematogenous spread from the primary site of infection (lungs) or from contiguous anatomical sites, such as the paranasal sinuses (McCarthy et al 2014). Focal lesions or a brain abscess are the predominant findings (Barrera-Herrera et al 2015), while cerebral infarction caused by septic embolism, vascular thrombosis, or mycotic aneurysms are less frequent (McCarthy et al 2014), and meningitis (without parenchymal involvement) is rarely reported (Antinori et al 2013). Microscopically, Aspergillus spp.…”
Section: 2mentioning
confidence: 99%